2020
DOI: 10.1002/adma.202002430
|View full text |Cite
|
Sign up to set email alerts
|

Gas Diffusion Strategy for Inserting Atomic Iron Sites into Graphitized Carbon Supports for Unusually High‐Efficient CO2 Electroreduction and High‐Performance Zn–CO2 Batteries

Abstract: Emerging single‐atom catalysts (SACs) hold great promise for CO2 electroreduction (CO2ER), but the design of highly active and cost‐efficient SACs is still challenging. Herein, a gas diffusion strategy, along with one‐step thermal activation, for fabricating N‐doped porous carbon polyhedrons with trace isolated Fe atoms (Fe1NC) is developed. The optimized Fe1NC/S1‐1000 with atomic Fe‐N3 sites supported by N‐doped graphitic carbons exhibits superior CO2ER performance with the CO Faradaic efficiency up to 96% at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
148
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 182 publications
(156 citation statements)
references
References 52 publications
8
148
0
Order By: Relevance
“…By controlling the pyrolytic temperature, the NiN 4 , NiN 3 C, and NiN 2 C 2 sites could be fabricated at 600, 800, and 900 °C, respectively. It seems that the relationship between pyrolytic temperature and the N coordination number above is a general tendency, which has also been observed for Fe [44] and Cu [52] based samples. However, some works also reported that higher thermal activation temperature (e.g., 1000 °C) could promote MN 4 sites' synthesis, [53] thus producing more graphitic N in the carbonaceous frameworks, which induces charge redistribution and enhances electron-transport properties.…”
Section: Engineering the Coordination Environmentsupporting
confidence: 62%
“…By controlling the pyrolytic temperature, the NiN 4 , NiN 3 C, and NiN 2 C 2 sites could be fabricated at 600, 800, and 900 °C, respectively. It seems that the relationship between pyrolytic temperature and the N coordination number above is a general tendency, which has also been observed for Fe [44] and Cu [52] based samples. However, some works also reported that higher thermal activation temperature (e.g., 1000 °C) could promote MN 4 sites' synthesis, [53] thus producing more graphitic N in the carbonaceous frameworks, which induces charge redistribution and enhances electron-transport properties.…”
Section: Engineering the Coordination Environmentsupporting
confidence: 62%
“…[ 122 ] Recently, many non‐noble metals (Fe, Co, and Ni) SACs have been developed, they matched well with Au and Ag catalysts in terms of Faradaic efficiency for CO 2 RR. [ 123–128 ] For example, a family of isostructural porphyrinic MTV–MOFs had been fabricated by using TCPP and H 2 TCPP as building units with different metal (i.e., Fe, Co, Ni, Cu). CO was identified as the major product during the process of all four M–N–C model catalysts toward CO 2 RR.…”
Section: Applications Of Single‐atom Catalystsmentioning
confidence: 99%
“…fabricated isolated Fe atoms anchored on nitrogen‐doped porous carbon, achieving a high FE CO of 96% and a power density of 0.6 mW cm −2 . [ 19 ] Xie et al. developed a porous Pd nanosheet accompanied with enriched edges, resulting in 81.2% energy efficiency between CO 2 and formic acid reversible conversion.…”
Section: Figurementioning
confidence: 99%
“…OER happened during the charging process, which was accompanied by the deposition of Zn on the anode. [ 1,13,19 ] The discharge and charge polarization curves and the corresponding power density of a single Zn‐CO 2 battery are shown in Figure 3b,c. A maximum power density of 0.71 mW cm –2 can be achieved at a current density of 3.0 mA cm –2 , which is even larger than the Fe single‐atom based ones (Table S3, Supporting Information).…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation